Materia penal N° 00333-2016-0-09-01-JR-PE-04. Imputado: Miguel Antonio Cortez Orteza. Agraviada: Gloria Rosa Matos Valera. Delito: robo agravado. Órgano jurisdiccional: Cuarto Juzagado de Insvestigación preparatoria-Lima Norte / Materia constitucional N° 00411-2017-0-1903-JR-CI-02. Demandante: Brudith Ramírez de García. Demandandos: Hospital Regional de Loreto, y otros. Materia: proceso de cumplimiento. Órgano jurisdiccional:Segundo Juzgado Civil de Maynas - Arévalo Trujillo, Elvis Alejandro (2022)
On March 3, 2017, the plaintiff Brudiht Ramírez de García, a nurse by profession, files a lawsuit for a Compliance Process against the Director of the Regional Hospital of Loreto and the Regional Government of Loreto, before the Second Specialized Civil Court and Constitutional of Maynas. The claim of his claim is that the defendant officials and authorities comply with paying him the differential bonus for exceptional working conditions equivalent to 30% of his total remuneration, in accordance with the provisions of the first paragraph of article 184 of the Law N° 25303 – Annual Public Sector Budget Law for the year 1991. The court of first instance decides to declare the Compliance Action demand filed by Brudith Ramírez de García FOUNDED; Consequently, it orders that the defendant Regional Government of Loreto, within ten days of being notified of the Resolution, comply with the payment of the integral differential bonus for the exceptional working conditions equivalent to 30% of its total remuneration, as well as the reinstatement of the amounts not received from January 1991 to the present. Likewise, it orders the payment of the legal interests generated from the date the obligation was created, that is, from the month of January 1991, the year in which Law No. 25303 entered into force until the present. The defendant files an appeal. The Civil Chamber of Loreto, in a second instance ruling, resolves to REVOKE the ruling that fails, declaring the Compliance Action demand filed by Brudith Ramírez de García founded (…); consequently, REFORMÁNDOLA declares the Compliance demand IMPROPER. The plaintiff files an appeal for constitutional tort. Finally, the magistrates Ramos Núñez, Ledesma Narváez and Espinoza-Saldaña Barrera, through an interlocutory ruling, decided to declare the constitutional tort appeal IMPROPER.